Electronics reliability assessment of future power fusion machines: Neutron interaction analysis in bulk silicon. (November 2021) - Autran, J.L.; Munteanu, D.
Abstract: The interactions of high energy neutrons produced in D-D and D-T nuclear fusion reactions with natural silicon have been investigated through direct calculation using nuclear cross section libraries, MCNP6 and Geant4 numerical simulations. From the systematic simulation and particle tracking of 5×10 8 neutrons incident on a 1 cm 2 ×20 μm bulk target, we provide a detailed analysis of all interactions (elastic, inelastic, nonelastic) per type of reacting silicon isotope and an exhaustive classification of all neutron-induced secondary products as a function of their type, energy, linear energy transfer and range in silicon. Implications for reliability of the electronics in future power fusion machines are discussed based on these first evaluations. Highlights: Interactions between natural silicon, 2.45 MeV and 14 MeV neutrons are studied. At 14 MeV, 40% of elastic, 30% of inelastic and 30% of nonelastic events are produced. At 2.45 MeV, 75% of elastic, 25% of inelastic and no nonelastic events are produced. Implications for reliability assessment of the electronics in future power fusion machines are discussed.